Thermal runaway risk analysis in styrenic block copolymer production. Issue 3 (12th December 2020) - Rodriguez‐Guadarrama, Luis
Abstract: Styrenic butadiene block copolymers are an important family of commercial materials in the category of thermoplastic elastomers. These elastomers are made of separate polymeric blocks. At the beginning, there is a hard polystyrene block and in the middle, there is a polybutadiene block. Butadiene is the monomer in highest concentration in regular styrenic block copolymers. The main risk linked to the production of styrenic block copolymers on an industrial scale is the loss of control of the reactor temperature, which may lead to a temperature increase resulting in a pressure increase above its design pressure during the formation of the polybutadiene block. Fatal accidents have occurred in some chemical plants due to runaway butadiene polymerization. Critical parameters that characterize thermal runaway for the anionic polymerization of butadiene in batch reactors were established for different scale reactors: laboratory, pilot and industrial reactors. Runaway and safe conditions are identified based on the pattern of temperature and conversion trajectories near complete butadiene conversion. The resulting is useful for establishing runaway diagrams for the anionic polymerization of butadiene in batch reactors using dimensionless parameters: reaction sensitivity and cooling intensity.